Employing Intelligence for Detecting the Emotions Using Efficient Machine Learning Algorithms - Asha, P.; Suresh, L. Padma; Gani, Abdul Mohamed Ibrahim; S, Praveen; Sai, Alagingi Deepak; Mathivanan, G. (2024 International Conference on Science Technology Engineering and Management (ICSTEM), 2024)
This work introduces the sophisticated voice-controlled assistant integrating voice recognition along with, Natural Language Processing for effective identification and retrieval of essential main words, along with Deep Learning techniques for effective analysis. It captures user voice commands, converts text to speech, performs web searches, and opens Google Chrome. Computer vision capabilities include real-time object detection with web scraping for pricing information. Emotion detection using pre-trained models enhances human-centric interaction. The assistant interfaces with the Bard API for dynamic conversational exchanges, ensuring a responsive user experience. Modular design allows easy integration of additional functionalities, adapting to future enhancements. The Multipurpose AI Assistant aims for a seamless and user-friendly interface, showcasing the convergence of cutting-edge technologies for intelligent voice-controlled assistance.